Making as Enquiring: Performing Making as a Means of Answering Research Questions - Sung, Karen Jiyun (Imaginations, 2024)
Practice-based research and well-researched creative practice are not the same. The former shapes its question through practice, while the latter refines its answer through research. The paper aims to emphasize the position of the practice-based research method as a strong companion to written methods rather than a replacement.This paper exemplifies the distinctiveness of practice-based participatory research when conducted with culturally specific groups, South Korean in this case, where drawing led to a firm illumination of self-identities where traditional research methods fall short. Through this investigation, the paper aims to contribute to discussions surrounding the diversification of what constitutes knowledge and its implications for research at large.